2017
DOI: 10.3390/educsci7040081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Educational Efficiency on National Competitiveness Based on Cross-National Data

Abstract: Abstract:The importance of education to national competitiveness and future development is self-evident. Resource input secures educational development. However, the efficiency of educational resources, their input-output ratio, and their effects on national competitiveness are matters of concern. This study aims to measure the efficiency of educational resources of a country within the scope of financial capacity. This study further evaluates the effects of educational efficiency on national competitiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…None of the macroeconomic variable had a significant impact on the competitiveness of the region. This result is similar to the findings of Liu and Xu (2017) whose estimation results for weak and very weak competitive economies showed that none of the macroeconomic variables significantly impacts their competitiveness. However, the overall significance of the model was confirmed by the F-value of 46.33707, which explained 97.66% of the variations of the competitiveness of countries in the region.…”
Section: South Africasupporting
confidence: 90%
See 2 more Smart Citations
“…None of the macroeconomic variable had a significant impact on the competitiveness of the region. This result is similar to the findings of Liu and Xu (2017) whose estimation results for weak and very weak competitive economies showed that none of the macroeconomic variables significantly impacts their competitiveness. However, the overall significance of the model was confirmed by the F-value of 46.33707, which explained 97.66% of the variations of the competitiveness of countries in the region.…”
Section: South Africasupporting
confidence: 90%
“…The Growth rate of the real GDP was found to have an insignificant negative impact on the competitiveness of African economies, which is opposite the results of Rosu and Roman (2018) of a significant positive impact of GDP growth rate on the competitiveness for the transition and innovative-driven CEE economies. This result also conflicts the findings of Liu and Xu (2017) of a significant positive impact of GDP per capita on the competiveness of 53 countries. The result might not be unconnected with the quality of growth we have in Africa, which is mostly not shared among the population.…”
Section: The All Africa Modelcontrasting
confidence: 82%
See 1 more Smart Citation
“…The study underscores the varying impact of education on competitiveness based on a country's development stage and location. It suggests that governments should align growth priorities with their developmental stage and regional context while considering competitiveness [38]. Veremchuk et al [39] assessed ten educational libraries and found that users have varied objectives, with students seeking textbooks and interaction, while scholars prioritize reference, research, and electronic resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [7], healthy adults carrying a 12 kg backpack for a short time experienced a significant reduction in the upper extremity perception and in all the macrovascular and microvascular hemodynamic parameters. The need to improve education efficacy for a better society has been previously emphasized [8], and reducing the physical stress arising from the daily transport of heavy backpacks can provide a considerable contribution.…”
Section: Introductionmentioning
confidence: 99%